Coup d’œil sur la recherche : Implantation d’un programme de formation à l’offre active de services en français auprès des futurs professionnels de la santé et des services sociaux dans une université canadienne. - Consortium national de formation en santé; van Kemenade, Solange (2022)

Nursing students’ well-being: A comparison of two canadian nursing programs in different linguistic contexts - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Vigier, Darcelle; Waddell, Candice; Graham, Jan Marie (Linguistic Minorities and Society, 2022)
Nursing programs are highly competitive and stressful environments; nursing educators are looking for ways to mitigate the negative consequences of demanding training programs. This article explores and compares the mental health status and sociodemographic and personal characteristics that influence the psychological distress of nursing and non-nursing students learning in either official language of Canada. An online and paper survey was administered during class time to 990 students, 186 of whom were in an undergraduate nursing program in one of two postsecondary institutions in Manitoba, Canada. Findings demonstrate that students in nursing programs are more likely to report poor mental health than students in other undergraduate programs and that nursing students in the French-language institution report poorer mental health outcomes as compared to nursing students in the English-language institution. Life satisfaction and high self-esteem are positively associated with well-being, whereas age, gender, and learning in a second language are risk factors contributing to anxiety. Keywords: mental health, risk behaviour, nursing students, linguistic minority, risk factors

NCLEX‐RN© preparation resources available online in French: An integrative review - Lalonde, Michelle; Prairie, Gabrielle; Vanderspank‐Wright, Brandi; Chartrand, Julie; Mcgillis Hall, Linda; Lamont, Michelle (International Nursing Review, 2022)
Background One entry to practice requirement for Canadian nurses is to successfully pass a licensing exam upon graduation from their educational program. In 2015, the American NCLEX‐RN replaced the Canadian entry to practice licensing examination which was offered in Canada's two official languages: English and French. The NCLEX‐RN was developed in English and later translated to French. Since its implementation, Francophone candidates and educators in Canada have reported a lack of preparatory resources available in their language and have had substantial lower NCLEX‐RN pass rates, consistently below 50%. Methods An integrative review using Whittemore and Knafl's framework was conducted between February and May 2019, and updated in September 2020, through online searches of CINAHL, PubMed, Science Direct and Google Scholar databases. Grey literature was included from 2012 onwards. Results are presented narratively. Results A total of 17 French language preparatory resources were found. These resources were categorised into four main groups: (1) What is the NCLEX‐RN; (2) What do I need to do prior to writing the NCLEX‐RN; (3) What is assessed through the NCLEX‐RN and finally, (4) How can I practice before taking the NCLEX‐RN Conclusion Limited French‐language NCLEX‐RN preparatory resources exist for Francophone candidates. Furthermore, practice questions in French are few compared to what is available in English Implications for Nursing and Nursing Policy Other countries may consider implementing an entry to practice exam such as the NCLEX‐RN because of its availability in both the French and English language, as well as the possibility of translating the exam to other languages, creating a potential market for this test around the globe. The lack of preparatory resources in French is a major concern to Francophone candidates undertaking such a high‐stakes examination in their language. Nursing stakeholders and policy leaders should acknowledge that such gaps place Francophone writers in a disadvantaged position in comparison to their Anglophone counterparts.

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

Boîte à outils virtuelle de soins culturellement adaptés pour les francophones dans les foyers de SLD - Réseau du mieux-être francophone du Nord de l’Ontario (2022)

Recommandations de l’étude de besoins sur les foyers de soins de longue durée du Nord de l’Ontario - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)
Ce rapport a pour objectif de faire la mise à jour de recommandations tirées d’une étude réalisée par le Réseau du mieux-être francophone du Nord de l’Ontario (Réseau) en 2017. Les actions comprennent, entre autres, l’identification de foyers pour l’offre de services en français ainsi que l'accompagnement de foyers pour l'amélioration des services en français et le développement de stratégies pour mettre en œuvre des soins culturellement adaptés. Dans le cadre de ce rapport, nous avons souligné les thèmes qui ont été partagés avec nous ou dont nous avons pris connaissance par l’entremise de notre travail avec nos partenaires. Le but est de capter l’essence de la réalité de l’expérience des francophones résidant dans les foyers de soins de longue durée, ainsi que d’offrir des pistes d'actions qui nous permettront d’assurer une meilleure planification des services en français dans les foyers de soins de longue durée dans le Nord de l’Ontario.

Recommendations from the Northern Ontario Long-Term Care Homes Needs Study - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)
The purpose of this report is to provide an update on the recommendations from a study completed by the Réseau du mieux-être francophone du Nord de l’Ontario (Réseau) in 2017. The actions include identifying homes where French-language services could be offered, accompanying those homes where French-language services could be improved and developing strategies to implement culturally appropriate care. In the context of this report, we have identified themes that were shared with us or that we became aware of through working with our partners. The goal is to capture the essence of the real experience of Francophone residents in long-term care homes as well as offer courses of action which will allow us to ensure better planning of French language services in long-term care homes throughout Northern Ontario.

Rapport sommaire de la conférence sur les langues de la santé. - Société Santé et Mieux-être en français du Nouveau-Brunswick (2022)